Pelatihan Penerapan Modul Ajar Melalui Strategi Pembelajaran Terdiferensiasi Bagi Guru-Guru SD Negeri Malangrejo - Titi Anjarini; Suyoto; Arum Ratnaningsih; Elis Yohana (Yayasan Kajian Riset Dan Pengembangan Radisi, 2023)
Based on the results of observations and interviews, data obtained that there are several problems, namely 1) students and teachers are still not used to implementing learning with differentiated learning strategies, 2) there are not many teachers trained in creating learning with differentiated learning strategies, 3) the decline in student enthusiasm for learning is because students are used to it. in classical learning in the 2013 curriculum, 4) there are no facilities that support differentiated learning that is tailored to the character and interests of students, 5) this means that learning is not optimal in groups and is varied. The objectives of this activity are 1) familiarizing teachers and students with applying teaching modules through differentiated learning strategies, 2) increasing awareness of teachers and students in implementing learning according to teaching modules through differentiated learning. The method used in this research is in the form of training and teacher response questionnaires about training. The average results obtained from the questionnaire before training were 1.6. Meanwhile, the questionnaire results after training had an average of 3.3.